Fenomena De-Influencing dalam Gaya Berbusana Minimalis Pada Gen Z di Indonesia - Krisma Desita; Fitri Adellia; Rauly Sijabat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The phenomenon of de-influencing is the latest trend on social media, where individuals or content creators encourage their audiences to be more selective in purchasing products, especially in the fashion industry. This study aims to understand the meaning of de-influencing, the reasons why someone does it, and how Generation Z in Indonesia applies a minimalist fashion style. This study used a descriptive qualitative method by collecting data through in-depth interviews with six Gen Z informants who are active on social media and live a conscious consumption lifestyle. The data was analyzed using a thematic analysis approach to identify key themes related to the perceptions, experiences, and application of de-influencing in minimalist fashion style. The results show that Generation Z views de-influencing as a way to reduce excessive consumption, increase self-awareness, and adapt their clothing style to their personal needs and values. They apply a minimalist style by choosing functional, durable, and versatile clothing, reducing the influence of rapidly changing trends, and avoiding impulse purchases. The main reasons for implementing this style are because they want to live a simpler, more efficient, and more environmentally friendly life, as well as reducing social pressure and the fear of missing out (FOMO) that comes from social media. These findings support previous research on the relationship between social media, conscious consumption, and minimalism, and provide insights into developing more ethical and environmentally friendly fashion marketing strategies for Generation Z.